Reducing Hydrocarbon in Place Uncertainty in Akasia Bagus Structure as Potential Field and Redevelopment Review - Tri Handoyo; Suryo Prakoso (Journal of Earth Energy Science, Engineering, and Technology, 2019)
The success of the discovery of new structure Akasia Bagus with potential L layer in 2009 at PT Pertamina EP's Jatibarang Field was followed up by the drilling infill wells with Plan of Development (POD) mechanism which is currently in the process of drilling the last well. The basis of the L layer hydrocarbon calculation in place on the POD is a static analysis. The wells currently produced are still able to flow with natural flow and enough production data since 2009 this structure was found. This study will present an analysis of production in the L layer of Akasia Bagus structure for Original Oil In Place (OOIP) updates using the conventional material balance method and then carry out the best development strategy to optimize oil production. Economic analysis is also carried out for reference in making decision on which scenario to choose. The conventional material balance method gets an OOIP value of 17.36 MMSTB, with the drive energy ratio being 5:3:2 for water influx : fluid expansion : gas cap expansion. Three (3) production optimization scenarios were analyzed, the results showed that the addition of 2 infill wells reached Recovery Factot (RF) of oil up to 23% of OOIP, minimal water production and attractive economic results.